Gambaran Perilaku Pengolahan Tinja Balita Dengan Kejadian Diare Di Kelurahan Galung, Kecamatan Tapalang Tahun 2024 - Muslimah, Muslimah; Ganing, Abdul; Ashari, Agus Erwin; Ahmad, Haeranah (Jurnal Kesehatan Lingkungan Mapaccing, 2026)
Diarrhea is a communicable disease that frequently causes Extraordinary Events (KLB/outbreak) and is often accompanied by death in Indonesia. One of the factors associated with the incidence of diarrhea is the unhygienic or indiscriminate disposal of feces, which is closely related to human behavior. This study aims to describe the level of knowledge, attitudes, and actions regarding toddler feces management in relation to the incidence of diarrhea in Galung Village, Tapalang District, in 2024. This research used a descriptive method with total sampling, involving 106 mothers of toddlers as respondents. Data were collected through direct interviews using a questionnaire. Based on the results, of the 106 respondents, 74 (69.8%) had toddlers who experienced diarrhea. Respondents with good knowledge who experienced diarrhea numbered 57 (69.51%); respondents with a disapproving attitude who experienced diarrhea numbered 68 (72.3%); and respondents with insufficient actions who experienced diarrhea numbered 48 (67.6%). It is concluded that the majority of mothers had good knowledge but still experienced diarrhea, most mothers held disapproving attitudes toward safe feces management, and most mothers' actions in feces management were still insufficient. It is recommended that local health centers routinely conduct health education targeting safe toddler feces management practices, particularly focusing on areas with the highest rates of insufficient responses. The suggestion from this research is that the public is expected to pay more attention to the processing of toddler feces so that the incidence of diarrhea in toddlers can be treated early